Fenomena Sosial Free Sex Pada Masyarakat Banda Aceh : Studi Efektifitas Sosialisasi Qanun No. 14 Tahun 2003 Tentang Khalwat di Kota Banda Aceh - Asmaunizar (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2019)
Research study of the effectiveness of socialization qanun No. of 2003 on khlawat in Banda Aceh was conducted using field research (Field Research) which are qualitative, discuss three issues How effective socialization Qanun of 2003 on Seclusion in Banda Aceh, ). What factors inhibit socialization Qanun of 2003 on Seclusion in Banda Aceh and ). Factors that influence the behavior of free sex on the citizens of the City of Banda Aceh. This research is. The approach used in this study is a socio-juridical. Based on the analysis of the study of the three issues raised, it was found that the First, socialization qanun seclusion has been running since at sahkannya Qanun is, but the implementation is a lot going on both constraints of the human factor and the factor of the entertainment spots and areas prone to triggering life free dikalangkan sex Banda Aceh society. Secondly, many of the factors that inhibit socialization Qanun of 2003 on Seclusion in Banda Aceh, the start of many persons who membackengin places of entertainment to the fact that calls into the city of Banda Aceh that potential in increasing seclusion and free sex offense, Banda Aceh is the provincial capital of Aceh, and deviant behavior to promiscuity can be mushrooming, it is also because the number of places that can be used as a place for seclusion and perform promiscuity freely so that the perpetrators committed the offense. Third, many factors influence the behavior of free sex on the citizens of Banda Aceh, which are due to the lack of religious knowledge and lack of oversight of the family and the environment. The conclusion from this study is that the government should impose Banda Aceh community improvement program should be even more incentive to impose a curfew to suppress the occurrence of free sex among people in Banda Aceh.